B cells in transplant tolerance and rejection: friends or foes? - Schmitz, Robin (Transpl Int, 2020)
Our understanding of the role of B cells in organ transplantation remains incomplete and continues to grow. The majority of research has focused on the detrimental role of antibodies that drive the development of pathogenesis of the transplanted organ. However, it has been shown that not all donor-specific antibodies are harmful and in some circumstances can even promote tolerance through the mechanism of accommodation. Furthermore, B cells can have effects on transplanted organs through their interaction with T cells, namely antigen presentation, cytokine production, and costimulation. More recently, the role and importance of Bregs was introduced to the field of transplantation. Due to this functional and ontogenetic heterogeneity, targeting B cells in transplantation may bring undesired immunologic side effects including increased rejection. Therefore, the selective control of B cells that contribute to the humoral response against donor antigens will continue to be an important and challenging area of research and potentially lead to improved long-term transplant outcomes.